EXPLOITATION OF LEGAL LOOPHOLES BY FIXED-TERM EMPLOYMENT WORKERS IN THE CONTEXT OF COMPENSATION PAYMENTS FROM THE PERSPECTIVE OF LEGAL UTILITY - Saputra, Diwa; Adam, Richard C. (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The Fixed-Term Employment Agreement is a form of employment relationship limited by a specific period, as regulated under Law Number 13 of 2003 on Manpower, as amended by Law Number 11 of 2020 on Job Creation, along with its implementing regulation, Government Regulation Number 35 of 2021. One of the regulatory innovations introduced by these instruments is the concept of compensation payment for Fixed-Term Employment Agreement workers, regardless of the reason for the termination of employment. However, in practice, this provision has created a legal loophole that may be exploited by workers to obtain compensation even when, in substance, such entitlement does not meet the criteria of fairness. This study aims to analyze the forms of legal loophole exploitation by Fixed-Term Employment Agreement workers in the implementation of compensation payments and to examine this phenomenon from the perspective of legal utility. The research employs a normative juridical method using both statutory and conceptual approaches. The results indicate that the lack of normative clarity in Government Regulation Number 35 of 2021 particularly concerning the conditions for granting compensation and the mechanisms of its supervision has opened opportunities for misuse of rights by workers. From the perspective of legal utility, this demonstrates that the current regulatory framework has not yet fully achieved a balanced social benefit between workers and employers.